Evaluation of the Success Result Plants Revegetation in coal post-mining land Lati Site PT Berau Coal East Kalimantan - Istomo .; Yadi Setiadi; Alvi Nadia Putri (Jurnal Silvikultur Tropika, 2013)
Mining activities in the forest areas are done through the land use of forest areas. The activities of mining must always be followed by reclamation and revegetation to restore the condition of damaged forest area as a result of mining efforts and forest areas can serve again in line with aimed. Revegetation is an effort to repair and restore the damaged vegetation by planting and maintenance activities on the grounds of forest areas former use. Evaluation needs to be done to find out the status of successful revegetation has been done by mining company. Purposes of this research are to assess the successful status of revegetation on post-mining land based on survival rate and plants performance of Acacia mangium on Block Q3 East Elevation 60 Lati Site of PT Berau Coal East Kalimantan. Observation also held to find out the causes of ineffective growth by result of soil analysis on post-mining land, and also to give recommendations of revegetation improvements.The result showed that the success of revegetation status on Block Q3 East Elevation 60 Lati Site is not successful based on survival rate and performance of planted plants. It is caused by the average values of growth and health plant percentage which lower than 80%. The average value of growth percentage is 79,31% and health plant percentage is 71,62%. The main factor of this condition is failure characteristics of soil revegetation which unsupport properly for the growth of plants. The level of soil acidity which appertain very acid soil can cause some important problems and it can be harmful to plants. Soil amendment and replanting vegetation should be done to improve revegetation on Block Q3 East Elevation 60 Lati Site PT Berau Coal East Kalimantan.Key words: Acacia mangium, evaluation, mining, revegetation